1999
DOI: 10.1021/tx9900369
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Human Serum Albumin by Sulfur Mustard in Vitro and in Vivo:  Mass Spectrometric Analysis of a Cysteine Adduct as a Sensitive Biomarker of Exposure

Abstract: To develop a mass spectrometric assay for the detection of sulfur mustard adducts with human serum albumin, the following steps were performed: quantitation of the binding of the agent to the protein by using [(14)C]sulfur mustard and analysis of acidic and tryptic digests of albumin from blood after exposure to sulfur mustard for identification of alkylation sites in the protein. The T5 fragment containing an alkylated cysteine could be detected in the tryptic digest with micro-LC/tandem MS analysis. Attempts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 26 publications
3
126
1
Order By: Relevance
“…After 2 h of incubation at 37°C, the mixture was passed through molecular mass cutoff filters (10 kDa) under centrifugation at 2772g to remove the enzyme. Under these conditions, pronase E digestion of albumin adducts is completed (Noort et al, 1999). The filtrate was subsequently analyzed by LC/MS/MS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 h of incubation at 37°C, the mixture was passed through molecular mass cutoff filters (10 kDa) under centrifugation at 2772g to remove the enzyme. Under these conditions, pronase E digestion of albumin adducts is completed (Noort et al, 1999). The filtrate was subsequently analyzed by LC/MS/MS.…”
Section: Methodsmentioning
confidence: 99%
“…This methodology, which has been applied successfully for the biomonitoring of exposure of humans to chemical warfare agents (Noort et al, 1999(Noort et al, , 2002, is based on the digestion of albumin by pronase E and subsequent selective detection of covalent adducts to the tripeptide cysteine 34 -proline-phenylalanine (CPF) by LC/MS/MS. Cysteine 34 is the only free thiol group in HSA and is capable of reacting with electrophiles.…”
mentioning
confidence: 99%
“…30,31) Mustard gas has been shown to alkylate a cysteine residue in human serum albumin, and the alkylation site was identified in a tryptic digest of mustard-gas-exposed albumin. 32) From an in vitro experiment using [ 14 C]-labeled mustard gas and cultured human cells, 15-20% of radioactivity was combined with keratin. 33) A time course study of the mustard gas adduct showed that the albumin adduct (S-2-hydroxyethylthioethyl)-Cys-ProTyr was detected until 7 days after exposure, and the N-terminal valine adduct in hemoglobin was detected after 28 days.…”
Section: Analysis Of Mustard Gas and Nitrogen Mustard Adductsmentioning
confidence: 99%
“…Methodologies for retrospective detection of exposure to CWs are available 29 . However, these advanced techniques were not available to the team to use for verification.…”
mentioning
confidence: 99%